The Relationship Between Torque, Angle, and Javelin Release Velocity for Beginners - Hussein, Ahlam (Journal of Physical Education, 2023)
This study aimed to determine the torque values of the body at the moment of the final throwing position, as well as the velocity and angle of release, and to identify the relationship between these three variables.The sample consisted of third-year students from the Department of Physical Education and Sports Sciences at the College of Basic Education, University of Mustansiriyah. The mean and standard deviation of the sample's age were (22.6) years (±0.68), weight (70.7) kg (±1.80), and height (173.2) cm (±0.95). The most important procedures for determining the measurements and the specific test of the research included measuring the height and weight of the sample and conducting the tests under study. The most important results showed a correlation coefficient between torque and javelin release velocity for students studying track and field in the javelin throw event. The most important conclusions are that there is a relationship between torque, release angle, and release velocity of the javelin, and the significance level is (0.005).